Encyclopedia of forensic and legal medicine - Byard, Roger W.; Payne-James, Jason (Amsterdam : Boston : Elsevier Academic Press, 2005)
Covers forensic and legal medicine. This encyclopedia offers practitioners in a forensic, medical, healthcare, legal, judicial, or investigative field authoritative overviews on a wide range of topics. It is suitable for undergraduates and graduates looking for an introduction to key fields and experts reading outside their specialization.
v. 1. A-Co -- v. 2. Cr-H -- v. 3. I-Ri -- v. 4. Ro-Z, index.
Includes bibliographical references and index.
Keywords: Covers forensic and legal medicine. This encyclopedia offers practitioners in a forensic, medical, healthcare, legal, judicial, or investigative field authoritative overviews on a wide range of topics. It is suitable for undergraduates and graduates looking for an introduction to key fields and experts reading outside their specialization; Encyclopedia; Forensic Medicine